The effect of demographic factors on occupational injuries. Issue 2 (3rd April 2017) - Salminen, Simo; Perttula, Pia; Ratilainen, Henriikka; Kuosma, Eeva
Abstract : Objectives . In Finland about 120, 000 occupational injuries occur annually, the cost of which is over EUR 2 billion per year. This is why it is reasonable to analyze the effect of demographic factors like gender, age, tenure and mother tongue on occupational injuries. Methods . The participants consisted of 1681 employees from four Finnish companies, who reported their injuries from the last 3 years. Results . Gender or mother tongue did not associate with injury involvement. Employees younger than 25 years of age were more often involved in injuries than employees aged over 55 (odds ratio [ OR ] = 2.69, 95% confidence interval [CI] [1.70, 4.23]). Employees with 2–10 years of experience in the company had a higher injury frequency than both novice and very experienced employees ( OR  = 2.01, 95% CI [1.60, 2.52]). Conclusions . This study showed that age was a more important factor in injury involvement than gender, tenure or mother tongue. However, age was closely related to experience in the company. Prevention measures in the companies should thus focus on novice employees.